The politics and governance of informal food retail in urban Africa - Resnick, Danielle (International Food Policy Research Institute, 2020)
Rapid urbanization in Africa south of the Sahara continues to highlight the importance of informal retailers as a source of both food and employment for the urban poor. The most recent Africa Agriculture Status Report emphasizes that, due to demographic and socioeconomic transformation in the region, the center of gravity of Africa’s food system is shifting to urban areas (AGRA, 2020). Informal retailers—including those who vend in open-air wet markets and hawk on pavements and streets—provide a critical link between agricultural producers and consumers. While the COVID-19 pandemic has dramatically highlighted the vulnerability of this constituency (Resnick et al., 2020), informal traders have long been victims of other public health, economic, and climate shocks (Battersby & Watson, 2019). To build the resilience of informal traders and enhance their contributions to urban food security, fundamental governance issues need to be addressed. This brief synthesizes research on informal traders conducted under the “Economywide Factors Affecting Agricultural Growth and Rural Transformation” flagship of the CGIAR Research Program on Policies, Institutions, and Markets (PIM) led by IFPRI. The research spanned Ghana, Nigeria, Senegal, and Zambia and involved comparative analysis across capital cities based on media events data, surveys with traders, and interviews with urban bureaucrats. In this way, traders’ experiences could be complemented with policymakers’ insights about bottlenecks and opportunities for reform